Migration of EEG Spike Foci and Epilepsy Outcome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2011)
Researchers at Chung Shan Medical University, Taichung, and other centers in Taiwan analyzed 969 EEGs from 463 children with epilepsy to determine outcome differences over 3 years between those with fixed epileptic foci and those with migrated foci.